Fouling Resistant CA/PVA/TiO2 Imprinted Membranes for Selective Recognition and Separation Salicylic Acid from Waste Water - Yu, Xiaopeng; Mi, Xueyang; He, Zhihui; Meng, Minjia; Li, Hongji; Yan, Yongsheng (Frontiers in Chemistry, 2017)
Highly selective cellulose acetate (CA)/poly (vinyl alcohol) (PVA)/titanium dioxide (TiO2) imprinted membranes were synthesized by phase inversion and dip coating technique. The CA blend imprinted membrane was synthesized by phase inversion technique with CA as membrane matrix, polyethyleneimine (PEI) as the functional polymer, and the salicylic acid (SA) as the template molecule. The CA/PVA/TiO2 imprinted membranes were synthesized by dip coating of CA blend imprinted membrane in PVA and different concentration (0.05, 0.1, 0.2, 0.4 wt %) of TiO2 nanoparticles aqueous solution. The SEM analysis showed that the surface morphology of membrane was strongly influenced by the concentration of TiO2 nanoparticles. Compared with CA/PVA-TiO2(0.05, 0.1, 0.2%)-MIM, the CA/PVA-TiO2(0.4%)-MIM possessed higher membrane flux, kinetic equilibrium adsorption amount, binding capacity and better selectivity for SA. It was found that the pseudo-second-order kinetic model was studied to describe the kinetic of CA/PVA-TiO2(0.2%)-MIM judging by multiple regression analysis. Adsorption isotherm analysis indicated that the maximum adsorption capacity for SA were 24.43 mg g−1. Moreover, the selectivity coefficients of CA/PVA-TiO2 (0.2%)-MIM for SA relative to p-hydroxybenzoic acid (p-HB) and methyl salicylate (MS) were 3.87 and 3.55, respectively.